Magnetic Activity of TESS Objects Observed in the LAMOST Medium-resolution Spectral Survey - Tianhao Su; Li-yun Zhang; Prabhakar Misra; Xianming L. Han; Yinpeng Wang; Wenjie Li; Zhongzhong Zhu; Qingfeng Pi; Hongpeng Lu (The Astrophysical Journal Supplement Series, 2025)
A combination of spectroscopic and photometric observations provides an excellent data sample for studying stellar chromospheric activity. We have combined LAMOST medium-resolution spectra with TESS 2 minute light curves and extracted over 530,000 spectra and 110,000 light curves from more than 40,000 stars. We have quantified the H α line intensity in each spectrum and found that 38,659 spectra from 7002 stars exhibited excess H α emission and that the intensity of stellar chromospheric activity increases with later spectral types. We also discovered that the boundary value between the saturated and unsaturated regions of chromospheric activity for different spectral type stars is around Ro = 0.1. By analyzing the TESS light curves, we identified 31,539 flare events from 4120 stars. Through these flare events, we determined that the flare-frequency proportion of stars increases with later spectral types. We have found that the power-law index of the flare-frequency distribution for F-, G-, K-, and M-type stars is around 2.0, while that for A-type stars is 1.3. Additionally, we observed that the amplitude of brightness variations caused by modulation due to starspot coverage ( R _eff ) is positively correlated with both the flare intensity and intensity of chromospheric activity and that the chromospheric activity was generally stronger in flare stars as compared to nonflare stars. We also found that within 300 pc, the proportion of chromospherically active stars and flare stars decreases with increasing distance from the Galactic disk. Finally, we discovered six flare events from the H α variation and estimated their energies.